Increasing the yield of drip-irrigated rice by improving photosynthetic performance and enhancing nitrogen metabolism through optimizing water and nitrogen management - Zhao, Lei; Tang, Qingyun; Song, Zhiwen; Yin, Yongan; Wang, Guodong; Li, Yuxiang (Frontiers in Plant Science, 2023)
Drip irrigation under plastic film mulching is an important technique to achieve water-conserving and high-efficiency rice (Oryza sativa) production in arid areas, but the grain yield of drip irrigation rice is much lower than the expected yield (10.9-12.05 t·hm-2) in practical production applications. Therefore, we hope to further understand the photosynthetic physiological mechanism of rice yield formation under mulched drip irrigation by optimizing water and nitrogen management during the growth period, and provide scientific reference for improving rice yield and nitrogen use efficiency under drip irrigation in arid areas. In 2020 and 2021, this study analysed the effects of water and nitrogen supply on the photosynthetic characteristics, nitrogen metabolism, yield, and NUE of two rice cultivars—T-43 (a drought-resistant; V1) and Liangxiang-3 (a drought-sensitive cultivar; V2)—under two water treatments (W1: limited drip irrigation, 10200 m3·hm-2; W2: deficit drip irrigation, 8670 m3·hm-2) and three nitrogen fertilization modes with different ratios of seedling fertilizer:tillering fertilizer:panicle fertilizer:grain fertilizer (N1: 30%:50%:13%:7%; N2: 20%:40%:30%:10%; N3: 10%:30%:40%:20%). The results showed that compared with other treatments, the W1N2 treatment resulted in 153.4-930.3% higher glutamate dehydrogenase (GDH) contents and 19.2-49.7% higher net photosynthetic rates (Pn) in the leaves of the two cultivars at 20 days after heading, as well as higher yields and NUE. The two cultivars showed no significant difference in the physiological changes at the panicle initiation stage, but the Pn, abscisic acid (ABA), IAA, gibberellin A3 (GA3), and zeatin riboside (ZR) levels of V1 were higher than those of V2 by 53.1, 25.1, 21.1, 46.3 and 36.8%, and 36.8%, respectively, at 20 days after heading. Hence, V1 had a higher yield and NUE than V2. Principal component analysis revealed that Pn and GDH were the most important physiological factors affecting rice yield performance. In summary, the W1N2 treatment simultaneously improved the yield and NUE of the drought-resistant rice cultivar (T-43) by enhancing the photosynthetic characteristics and nitrogen transport capacity and coordinating the balance of endogenous hormones (ABA, IAA, GA3, and ZR) in the leaves.